2019
DOI: 10.1038/s41598-019-40330-1
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2 ion channel promotes gastric cancer migration, invasion and tumor growth through the AKT signaling pathway

Abstract: Transient Receptor Potential Melastatin-2 (TRPM2) ion channel is emerging as a great therapeutic target in many types of cancer, including gastric cancer – a major health threat of cancer related-death worldwide. Our previous study demonstrated the critical role of TRPM2 in gastric cancer cells bioenergetics and survival; however, its role in gastric cancer metastasis, the major cause of patient death, remains unknown. Here, using molecular and functional assays, we demonstrate that TRPM2 downregulation signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…Both TRP channels and small GTPases have been implicated in increased tumor invasiveness through the induction of MMPs expression ( Betson and Braga, 2003 ; Yang and Kim, 2020 ). Indeed, TRPM2, TRPM7, TRPM8, TRPV2, and TRPC1 have shown to cause upregulation of MMP9 in a Ca 2+ -dependent manner in gastric, bladder, oral squamous, prostate and thyroid cancer cells respectively ( Monet et al, 2010 ; Okamoto et al, 2012 ; Asghar et al, 2015 ; Cao et al, 2016 ; Chen L. et al 2017 ; Chen Z. et al, 2017 ; Almasi et al, 2019 ). Additionally, TRPM2, TRPM7, and TRPC1 activity have been also correlated with MMP2 production in gastric, lung, pancreatic and thyroid cancer ( Asghar et al, 2015 ; Rybarczyk et al, 2017 ; Liu et al, 2018 ; Almasi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both TRP channels and small GTPases have been implicated in increased tumor invasiveness through the induction of MMPs expression ( Betson and Braga, 2003 ; Yang and Kim, 2020 ). Indeed, TRPM2, TRPM7, TRPM8, TRPV2, and TRPC1 have shown to cause upregulation of MMP9 in a Ca 2+ -dependent manner in gastric, bladder, oral squamous, prostate and thyroid cancer cells respectively ( Monet et al, 2010 ; Okamoto et al, 2012 ; Asghar et al, 2015 ; Cao et al, 2016 ; Chen L. et al 2017 ; Chen Z. et al, 2017 ; Almasi et al, 2019 ). Additionally, TRPM2, TRPM7, and TRPC1 activity have been also correlated with MMP2 production in gastric, lung, pancreatic and thyroid cancer ( Asghar et al, 2015 ; Rybarczyk et al, 2017 ; Liu et al, 2018 ; Almasi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TRPM2, TRPM7, TRPM8, TRPV2, and TRPC1 have shown to cause upregulation of MMP9 in a Ca 2+ -dependent manner in gastric, bladder, oral squamous, prostate and thyroid cancer cells respectively ( Monet et al, 2010 ; Okamoto et al, 2012 ; Asghar et al, 2015 ; Cao et al, 2016 ; Chen L. et al 2017 ; Chen Z. et al, 2017 ; Almasi et al, 2019 ). Additionally, TRPM2, TRPM7, and TRPC1 activity have been also correlated with MMP2 production in gastric, lung, pancreatic and thyroid cancer ( Asghar et al, 2015 ; Rybarczyk et al, 2017 ; Liu et al, 2018 ; Almasi et al, 2019 ). On the other hand, Rho and Rac GTPases activation has been correlated with increased MMPs expression in different cancer cell types ( Zhuge and Xu, 2001 ; Abécassis et al, 2003 ; Santibáñez et al, 2010 ; Jacob et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opening of TRP channels can promote Ca 2+ entry which activates downstream signaling pathways, such as Ca 2+ /calmodulin kinase II (CaMKII), mitogen-activated protein kinase (MAPK), AMPK and so on to control cell proliferation, apoptosis and migration [41,42]. Over the past two decades, several research groups including ours have identi ed six TRP channels (TRPC6, TRPM2, 5, 7, TRPV4, 6) that play an important role in GC development [6][7][8][43][44][45][46]. However, all these six TRP channels have been suggested as oncogene and tumor promoter in GC.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM4 also regulates mechanotransduction in cell migration via promotion of focal adhesion disassembly, activation of FAK activation and Rac1, and actin cytoskeleton reorganization (76). Recently, it has been shown that TRPM2 regulates migration and invasion of gastric cancer cells in vitro, and also tumorigenesis and expression of N-cadherin, snail, slug, integrins, and MMPs that are representative epithelial-mesenchymal transition (EMT) markers in vivo (77).…”
Section: Trp Channels In Cancer Metastasismentioning
confidence: 99%